Agriculture and landscape in Portugal - Firmino, Ana (Landscape and Urban Planning, 1999)
Landscape is the result of a dynamic process, which changes either due to natural causes or due to human impact. Therefore, we cannot expect landscapes to stay unchangeable, although some are evolving more quickly than others. Portugal is a mosaic of landscapes, partly because of different climatic conditions and orographic and morphologic genesis but also because of the impact of human activity, especially in agriculture. This article deals with the impacts of this sector on the landscapes, the consequences of which can be found not only in the ecosystems but also in the daily life of the people, in their jobs, in the abandonment of the land and in the change of mentality, related to the inadequate national policies and the overestimation of short-term economic pro®t
Keywords: agri-environmental measures; Environment; Portugal

Agriculture and landscape in Portugal (Landscape and Urban Planning, 1999)
Landscape is the result of a dynamic process, which changes either due to natural causes or due to human impact. Therefore, we cannot expect landscapes to stay unchangeable, although some are evolving more quickly than others. Portugal is a mosaic of landscapes, partly because of different climatic conditions and orographic and morphologic genesis but also because of the impact of human activity, especially in agriculture. This article deals with the impacts of this sector on the landscapes, the consequences of which can be found not only in the ecosystems but also in the daily life of the people, in their jobs, in the abandonment of the land and in the change of mentality, related to the inadequate national policies and the overestimation of short-term economic pro®t